221k views
5 votes
The solution of 3x - 4 ( x - 2 ) = 0 is ;

User Zanussi
by
5.2k points

2 Answers

0 votes

Explanation:

STEP 1:

Equation at the end of step 1

(3x - 4)2 = 0

STEP 2:

Solving a Single Variable Equation:

2.1 Solve : (3x-4)2 = 0

(3x-4) 2 represents, in effect, a product of 2 terms which is equal to zero

For the product to be zero, at least one of these terms must be zero. Since all these terms are equal to each other, it actually means : 3x-4 = 0

Add 4 to both sides of the equation :

3x = 4

Divide both sides of the equation by 3:

x = 4/3 = 1.333

One solution was found :

x = 4/3 = 1.333

User Hiroprotagonist
by
5.3k points
5 votes

Answer:

8

Explanation:

simplify the expression

3x - 4x+8 = 0

put like terms together 3x-4x = -x

-x + 8 = 0

add x on both sides

x = 8

happy holidays :)

please click the heart to give thanks :)

User Richrad
by
4.8k points